Arabian Sea Monsoon: Deep sea drilling in the Arabian Sea: Constraining tectonic-monsoon interactions in South Asia - Pandey, Dhananjai K.; Clift, Peter D.; Kulhanek, Denise K.; Andò, Sergio; Bendle, James A.P.; Bratenkov, Sophia; Griffith, Elizabeth M.; Gurumurthy, Gundiga P.; Hahn, Annette; Iwai, Masao; Khim, Boo-Keun; Kumar, Anil; et al. (My University, 2015)
The Arabian Sea in the northern Indian Ocean pre-serves regional sedimentary records of rifting, tectonic subsidence, and paleoceanographic history, and also provides archives of long-term erosion of the Himalaya since the start of collision between In?dia and Eurasia. Investigations reveal that drilling in this region can provide erosion records through analyses of the sediment cores, along with providing age control for the regional seismic stratigraphy. It is only by quantifying the volume of sedi?ment deposited in the fan that researchers can mass balance the volume of bedrock eroded from the mountains, constrained by thermochronology, with the volume of eroded rock deposited in the offshore and in the foreland basin.